Drug use among university students vulnerable to sexually transmitted infections: A quantitative study (Research, Society and Development, 2022)
Several studies indicate that there is greater vulnerability to acquiring sexually transmitted infections in the population that uses recreational drugs. Objective: this study aims to explore the relationship between the recreational use of psychoactive drugs in a sexual context among female, male and non-binary students at a university in the city of Rio de Janeiro. Method: this is a descriptive study with a quali-quanti approach, consisting of a semi-structured form delivered via the online platform "social network" 196 university students over 18 years of age in the city of Rio de Janeiro responded to the survey. Result: with this study it was possible to know the sexual behavior of this group of people and identify individual psychosocial factors. Conclusion: the characteristics of the social environment where this individual is inserted and the predominant beliefs of the community and about the treatment and normalization of HIV.